Evaluation of nitrous oxide emission by soybean inoculated with Bradyrhizobium strains commonly used as inoculants in South America - Obando, Melissa; Antonelli, Cristian; Casanave, Sheila; Maguire, Vanina; Torres, Daniela; Pérez, Gabriela; Bailleres, Matias Andres; Donadío, Florencia; Creus, Cecilia; Videla, Cecilia; Puente, Mariana Laura; Zilli, Jerri; et al. (Springer, 2024)
Aims The purpose of this work was to analyze the agronomic and environmental performance of soybean plants inoculated with the Bradyrhizobium strains widely used as soybean biofertilizers in South America and to determine if these strains possess any functional or taxonomic trait associated with the N2O emission.